2n+60=4n+6

Simple and best practice solution for 2n+60=4n+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n+60=4n+6 equation:


Simplifying
2n + 60 = 4n + 6

Reorder the terms:
60 + 2n = 4n + 6

Reorder the terms:
60 + 2n = 6 + 4n

Solving
60 + 2n = 6 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
60 + 2n + -4n = 6 + 4n + -4n

Combine like terms: 2n + -4n = -2n
60 + -2n = 6 + 4n + -4n

Combine like terms: 4n + -4n = 0
60 + -2n = 6 + 0
60 + -2n = 6

Add '-60' to each side of the equation.
60 + -60 + -2n = 6 + -60

Combine like terms: 60 + -60 = 0
0 + -2n = 6 + -60
-2n = 6 + -60

Combine like terms: 6 + -60 = -54
-2n = -54

Divide each side by '-2'.
n = 27

Simplifying
n = 27

See similar equations:

| 14x+6y=36 | | 56.75p+3.95=150.00 | | -20+15-22z=31 | | 2x+4(3x+8)=-80 | | y+2=-0.25(x+-4) | | 3y(y+8)=0 | | 280=14x | | 3(1-3d)=2(-4d-4) | | 56.75+3.95p=150.00 | | 4z+3=4z+3 | | x^4-8x^2-240=0 | | 9x+12=x-4 | | 8-2(-5+4)=10 | | y-2=-.25(x-4) | | -12+k=28 | | 5x+3=12x+15 | | 7-2x+6=4x-5 | | (4x-2)*(x+2)*0.5= | | 2n-3=5n+12 | | 25+1x=4+8x | | H(0)=x^2-6x+5 | | 5[x-2]=30 | | (4x-2)*(x+2)= | | s+2[s+3]+[4s-5]=148 | | 5x-22=77 | | 2y+2x^2=8x-8 | | y-0=.5(x-0) | | ax+5bx=7a-c+2ax | | 8x-10=85 | | -3=7-y | | 666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666+9d=2.88 | | -2(5y-10)-y=-4(y-3) |

Equations solver categories